Anchors for job quality: Sectoral systems of employment in the European context. (1st April 2010) - Damian Grimshaw; Steffen Lehndorff
Abstract : This paper argues that we can improve our understanding of the factors that shape job quality by interrogating the challenges facing sectoral systems of employment in diverse country contexts. Drawing on the work of the EU-funded Dynamo (Dynamics of national employment models) project, we describe an approach that includes paying attention to the set of social actors, product market rules, mix of technologies and skills and the character of the workforce in any given sector. Sectoral characteristics are shaped by the 'core' institutions constitutive of each national model but also retain distinguishing features. We then develop the argument that job quality is strengthened and sustained by key 'institutional anchors' and that these anchors vary in presence and strength by sector and country. A review of research on two specific sectors — care of the elderly and the automotive industry — shows that an inclusive model of industrial relations is a crucial anchor for job quality, but that its effects are contingent upon the specific production, employment and welfare characteristics of each sector.